The Dynamic Response Law of Bank Slope under Water-Rock Interaction - Yinchai Zhang; Huafeng Deng; Wei Wang; Lingling Duan; Yongyan Zhi; Jianlin Li (Advances in Civil Engineering)
During the reservoir operation process, the long-term security and stability of the bank slope is affected by dynamic response characteristics of its seismic action directly. Aimed at the typical bank slope existing in the actual reservoir environment, an experiment considering reservoir water level fluctuation and soaking-air-drying cyclic water-rock interaction has been designed and conducted while the cyclic loading test was performed in different water-rock cycles. Research results indicate the following: Firstly, in the process of water-rock interaction, the dynamic characteristics of sandstone show evident degradation trend, with the increase of the damping ratio and Poisson’s ratio and decrease of dynamic elastic modulus, and the former six water-rock cycle degradation effects are particularly obvious. Secondly, the numerical analog computation analysis of dynamic response in typical bank slope shows that as the water-rock interaction period is increased, the dynamic response of the slope hydro-fluctuation belt zone increases gradually, while the other parts weaken. Thirdly, under the long-term water-rock interaction process, the hydro-fluctuation belt zone gradually becomes a “soft layer” which is sensitive to the earthquake effect and dynamic response, resulting in a direct influence on long-term seismic performance of the bank slope. Therefore, it is necessary to make better protection for the bank slope hydro-fluctuation belt zone.